On the Occurrence of Multiple Rows of ‘Teeth’ in the Shell of the Dog-Whelk Nucella Lapillus - Cowell, E. B.; Crothers, J. H. (Journal of the Marine Biological Association of the United Kingdom, 1970)
The common dog-whelk, Nucella (= Thais , = Purpura) lapillus (L.), is often selected for ecological, physiological and genetical study. In recent years most workers have based their investigations on the work of Moore (1936; 1938a, b) and most have used his observation that ‘at the onset of maturity, growth of the (shell) lip ceases and instead the region near the lip thickens, while the lip itself becomes rounded and a series of rounded “teeth” develop on its inner side which still further occlude the opening’. It has been assumed that all animals showing these features are adult, and have ceased growing, for Moore goes on to say ‘occasional specimens are taken in which the presence of a second set of teeth within the marginal ones indicates that the original stoppage of growth was followed by a second slight growing period, this in turn being replaced by a second period of thickening and growth stoppage, but such specimens are too rare to be a serious source of error.’ This assumption has been incorporated into most subsequent reviews of shore ecology.